Consumer perceptions of sustainability: an exploratory study - Ferguson, K. E.; Hair, J. F.; Vinhas da Silva, R.; Oliveira-Brochado, A.; Mollah, M. M. H. (International Journal of Business, Marketing, and Decision Sciences, 2017)
This study looks at consumer intentions to purchase sustainable products and services, and how that is related to their experience, met expectations, reference groups norms, and information provided by eco-labels. A mixed method approach was used to develop hypotheses by conducting qualitative research to devise a theoretical consumer perceptions model based on the theory of planned behavior. The results reveal that U.S. consumers use eco-labels to guide their purchase behavior, have positive perceptions of sustainable products, exhibit a strong desire to purchase sustainable products, and want to be good stewards of the environment and society. Moreover, reference group influence is a strong predictor of sustainable product purchase behavior.